The Effect of Wordwall Digital Games on Students’ Vocabulary Achievement at Grade V of SD Negeri 4 Padangkerta - Lita, Ni Ketut Paula; Budiarta, Luh Gd Rahayu; Dambayana, Putu Eka (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2026)
The purpose of this study was to see whether the use of the Wordwall digital games as a learning medium had a significant effect on the vocabulary achievement of V-grade students at SD Negeri 4 Padangkerta. This study employed a quantitative approach using a quasi-experimental with a post-test only design. The participants of this study were fifth-grade students from the experimental and control groups with a total sample of 68 students. Data was collected through a post-test and analyzed using the SPSS 26.0 program. Based on the descriptive statistical analysis, the results showed that the experimental group achieved a higher mean score (M = 88.82) than the control group (M = 52.56). Furthermore, the results of the Mann–Whitney U test showed a significant difference between the experimental group and the control group (Sig. (2-tailed) = 0.000, p < 0.05), with a large effect size (r = 0.87), indicating that the treatment had a meaningful effect on students' vocabulary achievement. Therefore, the alternative hypothesis (Hₐ) was accepted, and the null hypothesis (H₀) was rejected. These findings imply that the use of Wordwall digital games as a technology-based learning can be an effective learning medium to support vocabulary development and enhance student engagement in English learning at the elementary school level.